A atuação política de Pinheiro Machado: o senador da conciliação do federalismo com a centralização na República Velha - Villagra Neto, Deomar (2012)
This paper intends to reflect on the political rule of Senator Pinheiro Machado, his sources of power and its role in ensuring regional interests without coliding with valorization of coffee policies that chacarterized the Old Republic. It also intends to analyze the historiography about the power of Pinheiro Machado and common senses formed without the major concern on to prove them or disprove them with sources. In pursuit of these goals, there will be a comparative analysis between historiography and primary sources about the Senator, and a study of the political structure of Rio Grande do Sul and Brazil s nascent Republic is essential to do so, the confrontation between regional demands an the centralism of the Union especially after the stipulation of the Policy of the Governors by President Campos Salles